OVER-EXPRESSION OF GENE ENCODING FATTY ACID METABOLIC ENZYMES IN FISH - Alimuddin Alimuddin; Goro Yoshizaki; Toshio Takeuchi; Odang Carman (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
Eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3) have important nutritional benefits in humans. EPA and DHA are mainly derived from fish, but the decline in the stocks of major marine capture fishes could result in these fatty acids being consumed less. Farmed fish could serve as promising sources of EPA and DHA, but they need these fatty acids in their diets. Generation of fish strains that are capable of synthesizing enough amounts of EPA/DHA from the conversion of α-linolenic acid (LNA, 18:3n-3) rich oils can supply a new EPA/DHA source. This may be achieved by over-expression of genes encoding enzymes involved in HUFA biosynthesis. In aquaculture, the successful of this technique would open the possibility to reduce the enrichment of live food with fish oils for marine fish larvae, and to completely substitute fish oils with plant oils without reducing the quality of flesh in terms of EPA and DHA contents. Here, three genes, i.e. Δ6-desaturase-like (OmΔ6FAD), Δ5-desaturase-like (OmΔ5FAD) and elongase-like (MELO) encoding EPA/DHA metabolic enzymes derived from masu salmon (Oncorhynchus masou) were individually transferred into zebrafish (Danio rerio) as a model to increase its ability for synthesizing EPA and DHA. Fatty acid analysis showed that EPA content in whole body of the second transgenic fish generation over-expressing OmΔ6FAD gene was 1.4 fold and that of DHA was 2.1 fold higher (P<0.05) than those in non-transgenic fish. The EPA content in whole body of transgenic fish over-expressing OmΔ5FAD gene was 1.21-fold, and that of DHA was 1.24-fold higher (P<0.05) than those in nontransgenic fish. The same patterns were obtained in transgenic fish over-expressing MELO gene. EPA content was increased by 1.30-fold and DHA content by 1.33-fold higher (P<0.05) than those in non-transgenic fish. The results of studies demonstrated that fatty acid content of fish can be enhanced by over-expressing gene encoding enzymes involved in fatty acid biosynthesis, and perhaps this could be applied to tailor farmed fish as even better sources of valuable human food.